2021
DOI: 10.1097/md.0000000000024186
|View full text |Cite
|
Sign up to set email alerts
|

Association of myostatin, a cytokine released by muscle, with inflammation in rheumatoid arthritis

Abstract: Myostatin is a cytokine produced and released by myocytes that might have an outstanding role not only in muscle wasting during cachexia but also in inflammation. Herein we explore the association between myostatin levels and inflammatory parameters in rheumatoid arthritis (RA). One hundred twenty-seven women without rheumatic diseases and 84 women with a diagnosis of RA were assessed in a cross-sectional study. Outcomes reflecting the activity of the arthritis including Disease Activity Score (DAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…Other studies have demonstrated overexpression of myostatin in the synovial tissue of RA patients [ 37 , 40 ]. However, an increase in the serum levels of this myokine has also been reported by us in RA, mainly in patients with moderate or severe disease activity [ 10 ].…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Other studies have demonstrated overexpression of myostatin in the synovial tissue of RA patients [ 37 , 40 ]. However, an increase in the serum levels of this myokine has also been reported by us in RA, mainly in patients with moderate or severe disease activity [ 10 ].…”
Section: Discussionmentioning
confidence: 66%
“…Santo et al found a prevalence from 13% to 30% in RA patients [ 29 ]. In this context, we previously reported a prevalence of rheumatoid cachexia of 14% in one study with a smaller sample of RA patients [ 10 ]. These differences in prevalence can be explained in part by the method of body composition assessment (DXA vs. bioelectrical impedance analysis or anthropometric measurements), the cut-offs used for diagnosis, the presence of comorbid diseases, and the disease characteristics of RA that can increase the risk of developing this condition (such as early vs. longer disease duration and a severe inflammatory status).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations